(untitled) (Web of Teachers: Inderscience Research, 2025)
This research explores the impact of interest rate changes on attracting investment to the bond market. Bond markets play a crucial role in the global economy, and interest rate fluctuations significantly influence investor behavior and the attractiveness of bonds. The study examines how rising or falling interest rates affect bond prices, yields, and investor sentiment. It also analyzes the relationship between interest rates and investment flows into various types of bonds, such as government, corporate, and municipal bonds. By investigating historical data, market trends, and case studies, this paper highlights the inverse relationship between interest rates and bond prices, the sensitivity of different bond types to interest rate changes, and shifts in investor preferences. The research provides insights for both investors and policymakers, offering recommendations for navigating interest rate fluctuations and maintaining a stable investment environment in the bond market.